The Effects Of Utilitarian And Hedonic Online Shopping Value On Consumer Perceived Value - Mohammad, Mohammad, Soepatini, Ph.D (2016)
study aims to determine how hedonic and utilitarian value influences on perceived value in shopping activities hrough e-commerce. Two questions that this research seeks to answer are: (1) the effect of utilitarian on perceived value of e-commerce consumer, (2) the effect of hedonic value on perceived value of e-commerce consumer. This research is quantitative research because the data obtained is in numbers derived from questionnaire. Non-probability sampling is used in taking the sample. The data were collected from 220 respondents' who have made a purchase through an e-commerce. The data were analyzed using multiple linear regression analysis. The result of the research shows: (1) utilitarian value has positive and significant effect on perceived value of e-commerce consumers. (2) hedonic value has positive and significant effect on perceived value of e-commerce consumers.